Exploring puberty experiences of young males (18-21 years) living in urban Pakistan: a qualitative inquiry - Shivji, Noureen Asif (2018)
Background: Adolescence is a time of dynamic change during which puberty transition occurs, which is characterised as bringing profound psychological transformation to adolescents’ identity, mental health and to impact on their overall behaviour. Literature has identified male adolescents to be less engaged in health promotion activities, and considered them a high risk population, particularly during puberty influencing their physical and psychological health outcomes, which may last longer. It is therefore essential that these young boys have good puberty experiences, as that will help to ensure better psychosocial adjustment in later life. However, socio-cultural factors play a significant role in Pakistan and other similar countries to create several barriers to puberty awareness and understanding of adolescent males, where only limited support is available for them in terms of enhancing their puberty experiences.